Exposure to graphic warning labels on cigarette packages: Effects on implicit and explicit attitudes towards smoking among young adults. Issue 3 (3rd March 2016) - Macy, Jonathan T.; Chassin, Laurie; Presson, Clark C.; Yeung, Ellen
Abstract : Objective: To test the effect of exposure to the US Food and Drug Administration's proposed graphic images with text warning statements for cigarette packages on implicit and explicit attitudes towards smoking. Design and methods: A two-session web-based study was conducted with 2192 young adults 18–25-years-old. During session one, demographics, smoking behaviour, and baseline implicit and explicit attitudes were assessed. Session two, completed on average 18 days later, contained random assignment to viewing one of three sets of cigarette packages, graphic images with text warnings, text warnings only, or current US Surgeon General's text warnings. Participants then completed post-exposure measures of implicit and explicit attitudes. ANCOVAs tested the effect of condition on the outcomes, controlling for baseline attitudes. Results: Smokers who viewed packages with graphic images plus text warnings demonstrated more negative implicit attitudes compared to smokers in the other conditions ( p = .004). For the entire sample, explicit attitudes were more negative for those who viewed graphic images plus text warnings compared to those who viewed current US Surgeon General's text warnings ( p = .014), but there was no difference compared to those who viewed text-only warnings. Conclusion: Graphic health warnings on cigarette packages can influence young adult smokers' implicit attitudes towards smoking.